HUBUNGAN LINGKUNGAN DAN AKTIFITAS AKADEMIK DENGAN TINGKAT STRES PADA REMAJA - Dyah Fajarsari; Sugi Purwanti; Artathi Eka Suryandari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Stress in adolescents that occurs in the educational environment can be summed up as a tension or crisis for students in participating in learning such as demands from parents to obtain good grades, environment like from the place, teachers and peers and academic activities. The purpose of this study was to determine the relationship between the environment and academic activities with stress levels. This research is an observational study with a cross-sectional approach. The population in this study were all female students of SMK Citra Bangsa Mandiri, the sampling technique used a purposive random sampling method, and the number of samples was 125 female students. The results of the study: most of the female students experienced stress (51%), most felt a conducive environment (53%), most experienced academic activities that were not conducive (56%), the correlation value between environment and stress level was 0.243 and the correlation value between academic activity with stress level is 0.275. Conclusion: there is a weak relationship between the environment and stress levels and there is a weak relationship between academic activities and stress levels.